Phase-Synchronizer based on gm-C All-Pass Filter Chain - JOVANOVIC, G. S.; MITIC, D. B.; STOJCEV, M. K.; ANTIC, D. S. (Advances in Electrical and Computer Engineering, 2012)
The use of analog CMOS circuits at high frequency has gained much attention in the last several years. At the heart of rapid prototyping of these circuits is the concept of using a versatile library of common RF function blocks. The blocks (cells) must be designed to be flexible in terms of drive requirements and loading. This paper presents the results of on-going research in development of phase-synchronizer as common RF function block, used in frequency and phase modulation, frequency synthesis, clock generation recovery, filtering, etc. The proposed circuit is based on series of voltage-controlled all-pass filter as delay chain, and enables phase regulation of analog input signals in wide range. Other characteristics of the input signal, such as amplitude and waveform are not deteriorated. The gm-C voltage-controlled all-pass filter is crucial block of the proposal. The IHP 0.25 um SiGe BiCMOS technology was used for design and verification of the circuit. Simulation results indicate that it is possible to obtain phase regulation in the wide frequency range, from 100 kHz up to 200 MHz.